2009
DOI: 10.1007/s00280-009-0927-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of lapatinib in patients with advanced biliary tree and hepatocellular cancer

Abstract: Lapatinib was well-tolerated. There was evidence of activity in HCC, but therapy with lapatinib did not meet the predefined efficacy rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(150 citation statements)
references
References 28 publications
6
138
0
6
Order By: Relevance
“…While early studies investigating novel agents targeting relevant signaling pathways demonstrated interesting antitumor activity in a small proportion of patients, the overall results have been disappointing, with outcomes largely similar to chemotherapy agents in the refractory setting ( Table 2) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). This may be in part due to the utilization of non-selected trials, where patients are eligible for enrollment regardless of their tumor genomic alterations.…”
Section: Targeted Therapies and The Role Of Cancer Genomics In Its Trmentioning
confidence: 87%
“…While early studies investigating novel agents targeting relevant signaling pathways demonstrated interesting antitumor activity in a small proportion of patients, the overall results have been disappointing, with outcomes largely similar to chemotherapy agents in the refractory setting ( Table 2) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). This may be in part due to the utilization of non-selected trials, where patients are eligible for enrollment regardless of their tumor genomic alterations.…”
Section: Targeted Therapies and The Role Of Cancer Genomics In Its Trmentioning
confidence: 87%
“…Phase II results indicate that lapatinib is well tolerated and shows preliminary evidence of antitumor activity in HCC (Ramanathan et al, 2006). Among 40 patients with advanced HCC, the response rate was 5%, median PFS was 2.3 months (95% CI 1.7-5.6) and median OS was 6.2 months (95% CI 5.1-N) (Ramanathan et al, 2009).…”
Section: Anti-egf/egfr Therapiesmentioning
confidence: 99%
“…Malka and colleagues reported their experience with a randomized phase II study comparing gemcitabine plus oxaliplatin alone with the same chemotherapy regimen in combination with cetuximab and demonstrated a higher 4-month PFS rate with the addition of cetuximab (44% versus 61%, respectively) [101]. Lapatinib, a dual EGFR-1 and HER-2/Neu inhibitor was tested in a phase II trial including both BTC and hepatocellular carcinoma patients [102]. In 17 evaluable patients with BTC, no responses were observed.…”
Section: Molecular Features and Targeted Therapies In Gbcmentioning
confidence: 99%